A pragmatic analysis of vulnerability in clinical research. (September 2017) - Wendler, David
Abstract: Identifying which subjects are vulnerable, and implementing safeguards to protect them, is widely regarded as essential to clinical research. Commentators have endorsed a number of responses to these challenges and have thereby made significant progress in understanding vulnerability in clinical research. At the same time, this literature points to a central contradiction which calls into question its potential to protect vulnerable subjects in practice. Specifically, analysis suggests that all human subjects are vulnerable and vulnerability in clinical research is comparative and context dependent, in the sense that individuals are vulnerable relative to others and in some contexts only. Yet, if everyone is vulnerable, there seems to be no point in citing the vulnerability of some individuals. Moreover, the conclusion that everyone is vulnerable seems inconsistent with the claims that vulnerability is comparative and context dependent, raising concern over whether it will be possible to develop a comprehensive account of vulnerability that is internally consistent. The solution to this dilemma lies in recognition of the fact that the practical significance of claims regarding vulnerability depends on the context in which they are used. The claims that appear to lead to the central contradiction are in fact accurate conclusions that follow from different uses of the term 'vulnerability'. The present manuscript describes this 'pragmatic' approach to vulnerability in clinical research and considers its implications for ensuring that subjects receive appropriate protection.